Hubungan Antara Persepsi Terhadap Penerapan Hukuman Dengan Motivasi Belajar Santri Pondok Pesantrenal-Muayyad Surakarta - Nuroniyah, Siti Robi'atun, Wisnu Sri Hertinjung, S.Psi, M.Psi, Psi (2016)
Motivation is needed in learning activities. Motivation is an encouragement to achieve learning success. It might be a boost of hope and ncouragement. One way to motivate by applying punishment, often used by teachers or parents. Motivation to learn can arise through punishment which is not excessive and applied at the right time. The purpose of this study is to determine relationship between perception of application of punishment with motivation to learn students islamic boarding school Al-Muayyad Surakarta. The method used is correlational study using a quantitative approach. Subjects used is students islamic boarding school Al-Muayyad Surakarta which amounted to 80 people and using purposive sampling technique. Measuring instruments used are learning motivation scale and perceptions of application punishment scale. The analysis method uses product moment correlation technique with SPSS (statistical product and service solution) 15.0 for windows program. Research result obtained the r value of 0.48; p = 0.000 (p <0.01), which shows the existence of very significant positive relationship between perception of application of punishment with motivation to learn which means that the higher perception of application of unishment with motivation to learn. Thus, conversely, the lower perception of application of punishment with motivation to learn based on the results of research known motivation to learn students islamic boarding school Al-Muayyad Surakarta is high. Motivation to learn to have the empirical mean (re) 129,57dan mean hypothetical (rh) 107,5. The effective contribution of the variable perception of application of punishment with motivation to learn by 23.04% and 76.96%, there are still other factors that influence the motivation to learn.